PENDAFTARAN HAK TANGGUNGAN TERINTEGRASI SECARA ELEKTRONIK DI KANTOR PERTANAHAN KOTA DEPOK - Elisabeth Putri; Dyah Setyorini (Reformasi Hukum Trisakti, 2022)
According to the Permen ATR/Ka.BPN Number 5 of 2020 Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency concerning Services Electronic Integrated Mortgage Rights, Electronically Integrated Mortgage (HT-el) is a set of procedures for servicing mortgage rights in the context of maintaining land registration data that  organized through an integrated electronic system. However, the implementation of electronic mortgage registration is in accordance with the Regulation of ATR/Ka.BPN Number 5 of 2020, starting from preparation to issuance of the Electronic Mortgage Certificate (HT-el Certificate), p. The Depok City Land Office is still in the development stage of electronic mortgage registration. Communication, availability of resources, attitude, and organizational structure all have an impact on this. Some challenges the readiness of the Depok City Land Office to improve internal data; and from external factors, such as the readiness of human resources, such as the PPAT and the Bank as the applicant, are the examples of external obstacles that cause the process of carrying out the Electronic Mortgage to be delayed, which will have an impact on the birth of the Mortgage. All barriers must be removed in the future, along with increased data verification and thorough training for all parties involved.